The Role of HMGB1 in Rheumatic Diseases - Dong, Yuanji; Ming, Bingxia; Dong, Lingli (Frontiers in Immunology, 2022)
HMGB1, a highly conserved non-histone nuclear protein, is widely expressed in mammalian cells. HMGB1 in the nucleus binds to the deoxyribonucleic acid (DNA) to regulate the structure of chromosomes and maintain the transcription, replication, DNA repair, and nucleosome assembly. HMGB1 is actively or passively released into the extracellular region during cells activation or necrosis. Extracellular HMGB1 as an alarmin can initiate immune response alone or combined with other substances such as nucleic acid to participate in multiple biological processes. It has been reported that HMGB1 is involved in various inflammatory responses and autoimmunity. This review article summarizes the physiological function of HMGB1, the post-translational modification of HMGB1, its interaction with different receptors, and its recent advances in rheumatic diseases and strategies for targeted therapy.